The apple of God's eye: a biblical account of holiness - Lebens, Samuel (Religious studies, 2025)
In this article, an exercise in Jewish philosophy, I propose a taxonomy that can account for and organize all of the many species of holiness that we find in the Hebrew Bible. Each species admits of precise definition. Moreover, the genus as a whole can be unified by a guiding metaphor, suggested by the Bible itself. Holiness, according to this metaphor, is bestowed by a certain type of gaze, and ultimately by occupying the centre of the field of God's attention.